2016
DOI: 10.1002/cpt.309
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B*38:02:01 predicts carbimazole/methimazole‐induced agranulocytosis

Abstract: Thioamides antithyroid-drugs (ATDs) are important in hyperthyroid disease management. Identification of the susceptibility locus of ATD-induced agranulocytosis is important for clinical management. We performed a genome-wide association study (GWAS) involving 20 patients with ATD-induced agranulocytosis and 775 healthy controls. The top finding was further replicated. A single-nucleotide polymorphism (SNP), rs185386680, showed the strongest association with ATD-induced agranulocytosis in GWAS (odds ratio (OR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…A similar observation was found in a Taiwanese study, which showed that HLA-B*38: 02 was less associated with PTU-induced agranulocytosis than with MMI-induced agranulocytosis. We did not find any association between the FMO3 gene and ATD-induced neutropenia, suggesting that the mechanism of ATD-induced agranulocytosis could be different from that of ATD-induced neutropenia, which is similar to a previous study of the Hong Kong population [8]. Sample sizes of PTU/MMI-induced agranulocytosis and neutropenia are rare, and future collaborative efforts are required to elucidate the role of genetic variants in these adverse drug reactions.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A similar observation was found in a Taiwanese study, which showed that HLA-B*38: 02 was less associated with PTU-induced agranulocytosis than with MMI-induced agranulocytosis. We did not find any association between the FMO3 gene and ATD-induced neutropenia, suggesting that the mechanism of ATD-induced agranulocytosis could be different from that of ATD-induced neutropenia, which is similar to a previous study of the Hong Kong population [8]. Sample sizes of PTU/MMI-induced agranulocytosis and neutropenia are rare, and future collaborative efforts are required to elucidate the role of genetic variants in these adverse drug reactions.…”
Section: Discussionsupporting
confidence: 71%
“…Another postulated mechanism is that neutrophils are against by the T cell-mediated reaction, and ATD can also have a direct toxic effect on the bone marrow [5][6][7]. To date, 3 genome-wide association studies of ATD-associated agranulocytosis have been performed in Taiwan (42 agranulocytosis cases [1,8,9]. Non-HLA genes also cause numerous drug-induced adverse effects through various pharmacokinetic and pharmacodynamic mechanisms [1].…”
Section: Novel Association Betweenmentioning
confidence: 99%
“…A similar study has been just reported from Hong Kong, China. Cheung et al [20] identified HLA-B*38:02:01 as the susceptibility locus of carbimazole-/MMI-induced AG, whereas the association with HLA-DRB1*08:03 did not reach significance. On the other hand, Hallberg et al [21] performed a GWAS in 234 European patients with nonchemotherapeutic-induced AG, including 39 ATD-induced AG, and found an association with HLA-B*27:05 and other single nucleotide polymorphisms on chromosome 6.…”
Section: Discussionmentioning
confidence: 99%
“…Since PTU‐induced agranulocytosis has been suggested to possess different genetic susceptibility from CMZ/MMI‐induced agranulocytosis by some researchers, we conducted a sensitivity analysis by excluding PTU‐induced agranulocytosis. Also, we conducted an additional sensitivity analysis by including studies that had used population controls …”
Section: Methodsmentioning
confidence: 99%